The Effectiveness of Parental Roles in Influencing Linguistic Development in Pre-School Children - Nugroho, Umar Hamid (Sekolah Tinggi Agama Islam Kuningan, 2024)
Language development is the ability to respond to sounds, follow commands, or speak spontaneously. In pre-school children, language skills begin to develop rapidly. Children have a vocabulary of 1,500 to 2,000 words by the age of 4 years. At the age of 5 years, children start to be able to answer the telephone, relate stories, and exchange information. Apart from that, children can also make questions, negative sentences, single sentences, compound sentences, and other forms of arrangement. Language development disorders are the most common disorders found in preschool children. This indicates that a child's language development can be optimal if verbal stimulation is carried out as early as possible, namely when the child is still in the womb. The method used in the formulation of this article is to use the literature review method, which in this study quotes from reliable journal sources that can support the process of formulating this article. The results found that there is a correlation between the effectiveness of the parental roles in influencing linguistic development in pre-school children.